Development of Lithuanian Property Valuers in the Scope of European Space - Galinienė, Birutė (Ekonomika, 2002)
In order to achieve long term success in the asset and business evaluation market it is important to have qualified property valuers. In the article, the level of qualification of the property valuers of Lithuania, it’s correspondence with the principles applied for the qualification of property valuers of the European countries and international and European standards are described. The comparative analysis of foreign countries and Lithuanian property and business valuation systems is presented. Problems of attestation of Lithuanian property and business valuers and related accreditation procedures of institution providing certification are analysed.Requirements prepared by the group of European valuations associations (TEGOVA) for the competence of the appraisers of Lithuania (requires for claimants; for examinations of certification the program of examinations; for the continue professional training; for the professional ethics) is the guide for the further reformation of the tern of professional training of the property actions and for the bringing of the qualification requirements closer to the international and Euro standards.